The Influence of Differences Temperature and Plastic Packaging Type Towards Level of Freshness Chickpeas (Phaseolus Vulgaris L) during Cold Storage - Pranata, Tude Popo; Pudja, Ida Ayu Rina Pratiwi; Kencana, Pande Ketut Diah (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Chickpeas are a type of legume that is easily respired, thus affecting the freshness of the product and causing a decrease in product quality. This study was to determine the effect of temperature differences and the type of perforated plastic packaging (PP and PE) on the freshness of green beans to get the best treatment. This study used a factorial randomized block design with two treatment factors. The first factor consisted of a temperature of 6 oC, 8 oC, and 10 oC. The second factor consisted of PP and PE plastic packaging types with eight perforated holes with 5 mm diameter and a plastic size of 11.4 cm x 24 cm that stored for 15 days. The results showed that the single treatment of temperature had a noticeable effect on the weight, the texture, total dissolved solids, the color L a b, the visual quality, 99lastic99ptic texture, 99lastic99ptic aromas, and overall reception. While the single treatment of packaging types has a real effect on weight shrinkage, total dissolved solids, and freshness tests. The interaction between packaging types and temperature has a noticeable effect on total dissolved solids, L and b colors, and freshness tests (visual quality, texture, aroma, and overall observation). Based on DMRT treatment (PE plastic and temperature 6℃) is the best cold storage, because the smallest weight shrinkage by 6.74%, embezzlement of color (a) by -0.66, color yellowing (b) by 1.61 and decrease in the average value of the best freshness test by 0.94 until the 15th day.